Difference in Reaction Times between True Memories and False Memories in a Recognition Task - Forai, Marta (My University, 2010)
Roediger and McDermott (1995) showed that false memories for words can be generated by showing a list of words to research participants, then asking them to recognize some of those words on a new list that also contains words semantically related to the original words but not present on the first list. Participants often think the semantically related words appeared on the first list. This study used a similar recognition task with twenty participants and measure their reaction times to words from the original list and to words frequently believed to have been on that list.
Color poster with text, tables, images, and graph.
Keywords: Posters; Memory--Research; Reaction time--Psychological aspects; False memory syndrome--Research